IMPROVING THE LITERAL READING ACHIEVEMENT OF GRADE VII STUDENTS OF SMPN 11 PALU THROUGH COOPERATIVE LEARNING - Yusuf, Rina (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2017)
Abstract The research aims at Improving the Literal Reading Achievement of Grade VII Students of SMPN 11 Palu through Cooperative Learning. The subject of the research was Grade VII Students of SMPN 11 Palu consisted of 26 students of Grade VII. The research was classroom action research which was conducted in two cycles where each cycle consisted of planning, implementation, observation and reflection. The data of this research were obtained from the results of the test and observation sheet, field notes, during the implementation of the action. The findings of the research showed that The students’ literal reading comprehension could be developed by implementing the Cooperative Learning. The students were able to answer the literal questions on their reading a text. During the process of implementing cooperative learning, I distributed the students equally and paid attention to the discussion in the group.. In addition, I used my time effectively to help the students during discussion time and give more chance for the low ability students. Comparing the result of students’ achievement in the first cycle, the students’ achievement on second cycle has significant development This can be studied from the result of teacher’s performance was categorized as good enough. The same thing happened for the students’ performance. The average score of the students in the test in cycle I increased from 62.12 to 79.32 in cycle II, while the mastery level improved from 38.46% in cycle I to 92.30% in cycle II.